Looking Northeast from California Boulevard to Thoroughbred Horse Unit (1949)
Legend on back of photo reads: 'A. Administration and Classroom Building, B. Library and Classroom Building, C. Gymnasium and Natatorium, D. Electrical Engineering and Air Conditioning Building, E. Jesperson, Heron and Chase Dormitories, 1. Prefab war surplus Buildings - 42 units being used on the campus for classroom purposes - these buildings have plywood floors installed on metal stringers as normal to 'Advanced Base Construction', 2. Classroom buildings, wood frame structures built by Division of Architecture in 1938 as temporary buildings, 3. Old wood frame shop buildings, single wall construction, must be demolished to make way for Engineering Building, 4. Fifty trailers installed for Veteran Housing in 1946, to be removed for site clearance for new Science Building, 5. Approximately 30,000 sq. ft. wood frame construction built in 1937 by N.Y.A. - approximately one-half dormitories, the other half classrooms, 6. Trailer and faculty housing unit constructed in 1946, five faculty housing units and 188 trailers - these units were moved in from San Miguel, California at the close of the war, 7. Two and three-room cottage units, war surplus buildings moved at the close of the war, also temporary dormitory facilities constructed by Navy during early part of the war, 8. Agricultural Education Building, condemned in 1936, second floor of this building occupied by Electronic Division housing approximately $250,000 of equipment, 9. Power House - heating capacity: two 100 h.p. boilers - one half of building occupied by ME laboratory housing diesel engine generating units - wood floor construction except in boiler room, serious fire hazard, 10. Cafeteria #1 constructed about 1909 - building should be demolished, serious fire hazard, 11. Deuel Dormitory housing 96 students, wood frame construction, stucco exterior - building in bad shape and should be abandoned and demolished.' Proper spelling of the family name is 'Jespersen'; it is commonly misspelled 'Jesperson'.